Inclusão escolar de alunos com deficiência na rede pública municipal de ensino em Imperatriz: uma análise a partir da implementação das Políticas Nacionais de Educação Especial do período de 2008 a 2021 - PEREIRA, Letícia de Jesus (2022)
This thesis results from the research on the inclusion of students with disabilities in the municipal public school system in Imperatriz and the process of implementation of National Policies for Special Education from an Inclusive Perspective. Therefore, the general objective is to analyze the process of implementing the National Special Education Policies for people with disabilities in the municipal public network of Imperatriz, from 2008 to 2021. The types of research are documentary, bibliographic and field, with a qualitative approach. The results showed that public educational policies, developed from an inclusive perspective at the national ambit, are partially fulfilled by the municipality. The elaboration of the PME represents one of these commitments since from the moment the National Policy on Special Education in the Inclusive Perspective (2008) came into force all other entities of the federation should adapt their documents and practices to insert students, target audience of this type of education, preferably in the regular network, in common rooms. Otherwise, as for educational practice the research revealed that these students often remain on the margins of the system, without access to education, owin to that the curricula do not comprehend them and are not adapted to them, which is inferred through the absence of continuing education offered to the teachers, but also through a certain lack of commitment on the part of teachers to inclusive ideals.